2014
DOI: 10.1155/2014/714674
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Lymphatic Imaging Modalities for Tumor Staging

Abstract: Tumor progression is supported by the lymphatic system which should be scanned efficiently for tumor staging as well as the enhanced therapeutic outcomes. Poor resolution and low sensitivity is a limitation of traditional lymphatic imaging modalities; thus new noninvasive approaches like nanocarriers, magnetic resonance imaging, positron-emission tomography, and quantum dots are advantageous. Some newer modalities, which are under development, and their potential uses will also be discussed in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…So-called sentinel lymph nodes (SLNs) are found in close distance to tumours and thus represent a gate for metastasis. 427 Mapping of SLNs is important for assessing the stage of cancer and for planning an efficient treatment. Different studies showed the possibility of SLN mapping using NIR-QDs [428][429][430][431][432] and demonstrated the possibility for an imageguided surgery for the resection of SLNs.…”
Section: These Results Demonstrated the Importance Of Appropriatementioning
confidence: 99%
“…So-called sentinel lymph nodes (SLNs) are found in close distance to tumours and thus represent a gate for metastasis. 427 Mapping of SLNs is important for assessing the stage of cancer and for planning an efficient treatment. Different studies showed the possibility of SLN mapping using NIR-QDs [428][429][430][431][432] and demonstrated the possibility for an imageguided surgery for the resection of SLNs.…”
Section: These Results Demonstrated the Importance Of Appropriatementioning
confidence: 99%
“…For example, 99MTC labelled liposomes for lymph node imaging. [34] Infections and their treatment: Infections are very diverse and caused by bacteria, fungi, parasites, viruses, etc. Beneficial effect is seen with lymphatic targeting because, viruses like HIV and parasites mainly reside in lymph nodes and lymph vessels.…”
Section: Applicationsmentioning
confidence: 99%
“…There are evidences that the oxidative stress in the central and peripheral nervous system (CECCHI et al, 2002;MOREIRA et al, 2007a) is responsible for mitochondrial dysfunction (MD) (BONDA et al, 2010a). It results in the development of various neurodegenerative disorders (AVILA, 2010), including AD (ZHU et al, 2013;MURTAZA et al, 2014) that can be categorized into two types: familial Alzheimer's disease (FAD) and sporadic Alzheimer's disease (SAD) (Table 2). FAD is found to be originated from mutations in at least one of the three genes recognized as amyloid precursor protein (APP) and presenilin-1 and -2(ps-1 and ps-2) (PRICE et al, 1998).…”
Section: Introductionmentioning
confidence: 99%